Curvilinear association of CGG repeats and age at menopause in women with FMR1 premutation expansions. Issue 8 (25th October 2014) - Mailick, Marsha R.; Hong, Jinkuk; Greenberg, Jan; Smith, Leann; Sherman, Stephanie
<x xml:space="preserve">Abstract</x> In a sample of post‐menopausal premutation carrier mothers of children with the full mutation of fragile X syndrome (n = 88), this study examined the co‐occurrence of the reproductive and psychiatric phenotypes associated with FMR1 premutations. Mean age at menopause was 43.1 years, and 35.2% of premutation carriers reported cessation of menses prior to age 40 (premature ovarian failure), but only 18% of carriers had been medically diagnosed by a physician as having Fragile X‐associated Primary Ovarian Insufficiency. There was a significant curvilinear association between CGG repeat length and age at menopause, with women who had mid‐range repeats having the earliest menopause, similar to the pattern that has been found for the psychiatric phenotype of the FMR1 premutation. © 2014 Wiley Periodicals, Inc.